Blood neurofilament light chain as a biomarker of MS disease activity and treatment response. (5th March 2019) - Kuhle, Jens; Kropshofer, Harald; Haering, Dieter A.; Kundu, Uma; Meinert, Rolf; Barro, Christian; Dahlke, Frank; Tomic, Davorka; Leppert, David; Kappos, Ludwig
Abstract : Objective: To assess the value of blood neurofilament light chain (NfL) as a biomarker of recent, ongoing, and future disease activity and tissue damage and its utility to monitor treatment response in relapsing-remitting multiple sclerosis. Methods: We measured NfL in blood samples from 589 patients with relapsing-remitting multiple sclerosis (from phase 3 studies of fingolimod vs placebo, FREEDOMS and interferon [IFN]-β-1a, TRANSFORMS) and 35 healthy controls and compared NfL levels with clinical and MRI-related outcomes. Results: At baseline, NfL levels (pg/mL) were higher in patients than in healthy controls (30.5 and 27.0 vs 16.9, p = 0.0001) and correlated with T2 lesion load and number of gadolinium-enhancing T1 lesions ( p < 0.0001, both). Baseline NfL levels, treatment, and number of new or enlarging T2 lesions during the studies predicted NfL levels at the end of study (all p < 0.01). High vs low baseline NfL levels were associated (estimate [95% confidence interval]) with an increased number of new or enlarging T2 lesions (ratio of mean: 2.64 [1.51–4.60]; p = 0.0006), relapses (rate ratio: 2.53 [1.67–3.83]; p < 0.0001), brain volume loss (difference in means: −0.78% [−1.02 to −0.54]; p < 0.0001), and risk of confirmed disability worsening (hazard ratio: 1.94 [0.97–3.87]; p = 0.0605). Fingolimod significantly reduced NfL levels already at 6 months (vs placebo 0.73 [0.656–0.813] and IFN 0.789 [0.704–0.884]), which was sustained until the end of the studies (vs placebo 0.628 [0.552–0.714] and IFN 0.794 [0.705–0.894]; p < 0.001, both studies at all assessments). Conclusions: Blood NfL levels are associated with clinical and MRI-related measures of disease activity and neuroaxonal damage and have prognostic value. Our results support the utility of blood NfL as an easily accessible biomarker of disease evolution and treatment response.